2006
DOI: 10.1529/biophysj.106.083667
|View full text |Cite
|
Sign up to set email alerts
|

The Transition between the B and Z Conformations of DNA Investigated by Targeted Molecular Dynamics Simulations with Explicit Solvation

Abstract: The transition between the B and Z conformations of double-helical deoxyribonucleic acid (DNA) belongs to the most complex and elusive conformational changes occurring in biomolecules. Since the accidental discovery of the left-handed Z-DNA form in the late 1970s, research on this DNA morphology has been engaged in resolving questions relative to its stability, occurrence, and function in biological processes. While the occurrence of Z-DNA in vivo is now widely recognized and the major factors influencing its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 134 publications
4
67
0
Order By: Relevance
“…In the previous TMD simulation study on the B-Z transition, 18 it was discussed that the energetic cost caused by the loss of WC pairing is compensated for by an increase in DNA-water hydrogen bonds. A similar trend was observed in our simulation, although the change in the number of hydrogen bonds is much smaller here probably because only local changes are involved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous TMD simulation study on the B-Z transition, 18 it was discussed that the energetic cost caused by the loss of WC pairing is compensated for by an increase in DNA-water hydrogen bonds. A similar trend was observed in our simulation, although the change in the number of hydrogen bonds is much smaller here probably because only local changes are involved.…”
Section: Resultsmentioning
confidence: 99%
“…16 A targeted molecular dynamics simulation method (TMD) 17 was also employed to study the pathway of the B-Z transition of a hexamer, [d(GpCpGpCpGpC)] 2 , in an explicit water environment, and the potential of mean force of the transition was evaluated by integration of the driving force. 18 A common feature of the transition pathways obtained from those simulations is that the B-Z transition occurs through a stretched intermediate state in a concerted manner. Stretching and parallelization of the phosphate backbone provides enough room for base rotation and a route for backbone rewinding in the opposite direction.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…From our studies we suggested that the stabilization of the Z-form is the result of a site-specific interaction by cations with the phosphate anions of the DNA backbone, vide supra. Molecular mechanics calculations, directed on the distribution of the cations over the Z-DNA surface, have also demonstrated that complexation preferentially occurs with the phosphate anions of d(C P G) and not with d(G P C) motifs of the helix [14]. With 31P nuclear magnetic resonance (NMR) measurements of the natural hexamer at different concentrations of Mg 2+ ions, an explicit selectivity between the different phosphates could be established.…”
Section: Synthesis and Characterization Of Phosphatemethylated Dnamentioning
confidence: 99%
“…Other aspects with respect to the salt-induced B-into Z-DNA transition are the corresponding conformational changes. A theoretical study has been given by Kastenholtz et al [14] using molecular dynamic simulations for a hexamer duplex with explicit solvation. Various models have been formulated for the B-into Z-dynamics.…”
Section: Synthesis and Characterization Of Phosphatemethylated Dnamentioning
confidence: 99%